Chinese zodiac signs the animal in all of us - Chen, C.J. (Chien-jen); Chen, Chen Jen; Cheng, Chuang Chi ([S.I] : Great Studio Production)
In China, the 12 zodiac signs are utilized. scientifically for recording the year and the hour. In ordinary life, they are used as folk arts and for fortune telling. For westerners, the 12 animal signs of the Chinese zodiac are interesting cultural emblems.
Copy available in DVD format
Executive producer, Chiou, An-san ; script , Mimi Chiou Huang, Ya-shin, Fred Steiner ; photography Chuang, Chi-cheng ; music, Chen, Shih-hsing
Narrator: Fred Steiner
Keywords: Astrology, Chinese